Establishing Relationship between Barriers and Facilitators of Supply Chain Integration: A Supply Chain Governance Model - Siswanto, Siswanto; Meiryani, Meiryani; Thoyib, Armanu; Zainal Abidin, Irwan Shah (ExcelingTech, 2019)
This research analyzes the influence of facilitators and barriers to the integration of supply chain on its performance. Moreover, it evaluates the relation among the facilitators and barriers of supply chain integration. The purpose behind the supply chain integration is to obtain efficiency in operational activities and effective strategic development through coordination in the supply chain. In order to achieve maximum efficiency, there is need for coordination and commitment among the partners in Supply chain to work mutually. There is need to recognize the external interdependencies when organizations work on protecting their self-interests internally. The study has used the focus of the research is on the internal and External governance efforts through the study of literature review. After conducting literature survey, research model is developed, and methodology is done. The results of the study related to the influence of facilitators and barriers on performance of supply chain are presented after research framework. The research will contribute to the literature by offering an understanding of the need for creating balance among the facilitators and barriers of integration in Indonesia.